Sonic place - a sonic augmented reality soundscape experience - Carvalho, José (2017)
This paper describes the conceptualization, technical and artistic development and the first results of the Sonic Place project. Sonic Place is an ongoing project centered in the relationship between the cultural heritage, sonic identity and sonic memories of specific places. Presenting both artistic and scientific objectives, the project tries to promote sonic ecology awareness and explores new technological possibilities for listening and discovering soundscape compositions. The project proposes a sonic augmented reality experience of current and past soundscapes that can be experienced by the use of a custom made mobile application. The project was presented at the 18th Biennial of Cerveira in Vila Nova de Cerveira, Portugal, 2015 and on the 6th Semibreve Festival in Braga, Portugal, 2016. In total, more than 100 on site recordings were made, 20 musical compositions were developed and 224 users experienced the application.